Efficient Labeling Of Mesenchymal Stem Cells For High Sensitivity Long-Term MRI Monitoring In Live Mice Brains - Ali AAA (Dove Medical Press, 2020)
Ahmed Atef Ahmed Ali,1 Rami Ahmad Shahror,2,3 Kai-Yun Chen2,3 1TMU Neuroscience Research Center – NeuroImage, College of Medicine, Taipei Medical University, Taipei 110, Taiwan; 2Ph.D. Program for Neural Regenerative Medicine, College of Medical Science and Technology, Taipei Medical University and National Health Research Institutes, Taipei 110, Taiwan; 3Center for Neurotrauma and Neuroregeneration, Taipei Medical University, Taipei 110, TaiwanCorrespondence: Ahmed Atef Ahmed AliTaipei Medical University, No. 250, Wuxing Street, Xinyi District, Taipei 110, Taiwan ROCTel +886-2-2736-1661 ext 3215Email ahmed.atef.dr@gmail.comBackground: Regenerative medicine field is still lagging due to the lack of adequate knowledge regarding the homing of therapeutic cells towards disease sites, tracking of cells during treatment, and monitoring the biodistribution and fate of cells. Such necessities require labeling of cells with imaging agents that do not alter their biological characteristics, and development of suitable non-invasive imaging modalities.Purpose: We aimed to develop, characterize, and standardize a facile labeling strategy for engineered mesenchymal stem cells without altering their viability, secretion of FGF21 protein (neuroprotective), and differentiation capabilities for non-invasive longitudinal MRI monitoring in live mice brains with high sensitivity.Methods: We compared the labeling efficiency of different commercial iron oxide nanoparticles towards our stem cells and determined the optimum labeling conditions using prussian blue staining, confocal microscopy, transmission electron microscopy, and flow cytometry. To investigate any change in biological characteristics of labeled cells, we tested their viability by WST-1 assay, expression of FGF21 by Western blot, and adipogenic and osteogenic differentiation capabilities. MRI contrast-enhancing properties of labeled cells were investigated in vitro using cell-agarose phantoms and in mice brains transplanted with the therapeutic stem cells.Results: We determined the nanoparticles that showed best labeling efficiency and least extracellular aggregation. We further optimized their labeling conditions (nanoparticles concentration and media supplementation) to achieve high cellular uptake and minimal extracellular aggregation of nanoparticles. Cell viability, expression of FGF21 protein, and differentiation capabilities were not impeded by nanoparticles labeling. Low number of labeled cells produced strong MRI signal decay in phantoms and in live mice brains which were visible for 4 weeks post transplantation.Conclusion: We established a standardized magnetic nanoparticle labeling platform for stem cells that were monitored longitudinally with high sensitivity in mice brains using MRI for regenerative medicine applications.Keywords: iron oxide nanoparticles, FGF21, regenerative medicine, tracking of cells, non-invasive imaging modality